Exploiting induced pluripotent stem cell-derived retinal pigment epithelium to unravel host-pathogen interaction in ocular tuberculosis: a reverse translational in vitro model - Putera, Ikhwanuliman; de Meerendonk, Sanne van; Nagtzaam, Nicole M.A.; La Distia Nora, Rina; Rombach, Saskia M.; de Steenwinkel, Jurriaan E.M.; Vingerling, Johannes R.; Dik, Willem A.; van Hagen, P. Martin (Frontiers in Ophthalmology, 2025)
Mycobacterium tuberculosis (Mtb) can infect the retinal pigment epithelium (RPE) cells. Current in vitro research models for ocular tuberculosis (OTB) only rely on RPE cell culture approaches. Until now it remains unclear why only a minority of patients with active systemic tuberculosis (TB) develops concurrent OTB. There is significant variation in the clinical manifestations of OTB, which is potentially influenced by ethnic differences and diversity in mycobacterial strains. To better understand the immunopathobiology of OTB, particularly an individual’s susceptibility to Mtb-infection and the specific host response, cell culture systems utilizing induced pluripotent stem cells (iPSC)-derived RPE cells offer a promising in vitro model to better mimic the disease. With this technology, RPE cells can be generated from specific patients of interest, enabling to test hypotheses in a bench to bedside or reverse manner. In this current study, we explore the utility of iPSC-derived RPE cells as an in vitro model for OTB. Such an approach would overcome drawbacks associated with the currently commonly used “general” RPE cell lines as disease model. The application of iPSC-derived RPE cells offers promising options for the identification of novel biomarkers and to study individualized drug screening methods for host-directed therapy of OTB, in order to restore and maintain vision in OTB patients with sight-threatening disease.